IMPLICATIONS OF HYDROSTATIC PORE PRESSURES AND HIGH CRUSTAL STRENGTH FOR THE DEFORMATION OF INTRAPLATE LITHOSPHERE - Zoback M.D.; Townend J. (My University, 2001)
Observations from deep boreholes at several locations worldwide indicate that (i) hydrostatic pore pressures persist to depths of as much as 12km in the upper crust, (ii) the brittle crust is in a state of failure equilibrium according to Coulomb frictional-failure theory, and (iii) bulk permeability is high - 10-17-10-16m2 - apparently due to fluid flow along critically stressed faults. As a result of these factors, the brittle crust is stronger than it would be under near-lithostatic pore pressure conditions.This result provides a constraint on models of lithospheric deformation. Postulating that the upper and lower crust and lithospheric mantle are totally coupled and that the total strength of the lithosphere is equal to the magnitude of tectonic driving forces (~3x1012Nm-1), we have calculated lithospheric strain rates under representative thermal and rheological conditions such that the integrated differential stress over the entire thickness of the lithosphere equals the plate driving force. For a strike-slip stress state and surface heat flow of 60+/-6mWm-2, average strain rates are approximately 10-18s-1 under hydrostatic upper crustal pore pressure conditions, and approximately 10-15s-1 under near-lithostatic pore pressures. The latter strain rates are higher than either observed geodetically using very long baseline interferometry (VLBI), or estimated on the basis of plate tectonic reconstructions. Hence we argue that hydrostatic upper crustal pore pressures enable lithospheric plates to behave rigidly over time scales of tens to hundreds of millions of years.
Keywords: CRUSTAL STRENGTH; FAULT MECHANICS; INTRAPLATE LITHOSPHERE; PRE PRESSURE; STRAIN RATE; STRESS